Decision Support System to Determine List of Drug Crimes in the Legal Territory of North Sumatra by Using the AHP (Analytical Hierarchy Process) Method - Gunawan Agus Permana (Institute of Computer Science, 2020)
Decision making is a key part of activities and information executives are not enough, data that is inaccurate and unable to analyze problems is a problem that occurs indecision making. Law is the most important system in implementing a series of institutional forces. To take a final decision whether a defendant is guilty or not for drug crime requires quite a long time so that in making a decision, a judge really needs as much information as possible. The Analytical Hierarchy Process (AHP) method has advantages in terms of decision making and accommodation processes for both qualitative and quantitative attributes for the decision making process of Analytical Hierarchy Process (AHP) which is also able to produce results that are more consistent, easily understood and used.